INCORPORATING ENTERPRENEURSHIP IN A PRODUCTION FUNCTION - Sujarwo Sujarwo; nuhfil hanani (Agricultural Socio-Economics Journal, 2016)
Entrepreneurship is an important factor which influences farmers’ production through the way how the rational farmers decide in allocating their inputs and make effective and efficient decisions facing risk and uncertainty in their production. Regarding this study, the first objective is to determine what is the essential factors can be applied to determine the level of entrepreneurship for the small scale farming production. The second objective is to utilize a fit production function incorporating entrepreneurship in the production function specified. The frontier production function is not fit with the data set; therefore, mean production function is selected for further analysis. Furthermore, the entrepreneurship that affects intercept in the model specified is the fit model with the variation of small-scale shallot production. It means that managerial skill is the most dominance factor in increasing production rather than entrepreneurship, which affects marginal productivity of inputs.